A prospective study of critical methods of amniotic fluid volume assessment - Gandhi, Mayur Rajendra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Adequate amniotic fluid volume (AFV) is required for fetal well-being and its assessment is taken as the single most important variable in fetal biophysical scoring system. I have critically evaluated various methods of amniotic fluid volume assessment keeping Amniotic Fluid Index (AFI) as the standard technique of Amniotic Fluid Volume (AFV) assessment. Methods: This was a prospective study where all patients were assessed for amniotic fluid volume at one sitting first by abdominal palpation followed by ultrasonographic assessment by various methods. Critical analysis of each individual method of amniotic fluid volume assessment was carried out for its sensitivity and specificity with regard to oligohydramnios, polyhydramnios and euamnios keeping AFI as the standard technique of AFV assessment. Effort was made to find out the best possible method of AFV assessment. Results: Almost all methods are reasonably effective in assessment of normal AFV. For assessment of oligohydraamnios 2cm x 2cm pocket and Maximum Vertical Pocket (MVP) depth (of 2 cm rule) methods are most suitable whereas other methods were found to be inappropriate. For assessment of polyhydramnios with regard to specificity MVP depth (>8cm) is reliable but with regard to sensitivity, subjective assessment and abdominal palpation are more reliable. Conclusions: When we compare all methods of AFV assessment, AFI and MVP depth (of 2 cm rule) have better correlation. Hence these methods are suggested for AFV studies in current clinical settings.